2021
DOI: 10.1051/e3sconf/202125103006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social media marketing in building relationship between brand loyalty of tourism products and products service quality

Abstract: Social media is an influential objective for most industries. Organizations in every sector are willing to implement this technique for achieving several business goals. Some of them are brand loyalty and service quality. The current study analyses these specific objectives in the tourism sector. The AIDA model has been considered in this scenario, where five hypotheses are generated. Instagram has been selected as the selected social media platform, as 45% of respondents preferred it. The study includes a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Hypothesis H2 is supported by data and revealed a statistically significant relationship between relationship marketing and social media. This result can be supported by previous studies conducted by (Jiaqi et al, 2021;Kotler et al, 2010;Albeza et al, 2013), who identified that social media provides an opportunity for customers to furnish fruitful feedback to the travel and tourism firms, which the firm could use to improve its relationship with the customers.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Hypothesis H2 is supported by data and revealed a statistically significant relationship between relationship marketing and social media. This result can be supported by previous studies conducted by (Jiaqi et al, 2021;Kotler et al, 2010;Albeza et al, 2013), who identified that social media provides an opportunity for customers to furnish fruitful feedback to the travel and tourism firms, which the firm could use to improve its relationship with the customers.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, incorporating social media strategy into relationship marketing has become the next frontier for all businesses to improve communication and build a more robust and stable relationship with customers. The advent of social media has allowed customers to share their opinions and experiences with marketers and build mutually beneficial relationships (Jiaqi et al, 2021;Kotler et al, 2010). Furthermore, based on (Albeza et al, 2013;Constantinides & Fountain, 2008;Mangold & Faulds, 2009), online social media shapes an atmosphere where customers can develop stable and rapid relationships in which both marketers and consumers can enthuse each other's ideas, feelings and understanding of the products or services.…”
Section: Relationship Marketing and Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Interest : with increase the interest of consumer amount by strategically introducing benefit and advantage rather than focusing on self-appraise or do traditional marketing, interest indicator consist of easy for accessing, consumer perception, clearly messages c. Desire : include create a desire for the goal that customer what it, beside that consist of to accomplish through well-knit information, product excellence, consumer desire, consumer curiosity d. Action : an element that facilitate consumer to accomplish their task, and lead consumer to conversion tunnel, confidence for buying product, influence other consumer, brand Image product AIDA Model is an formula which to plan a comprehensive advertisement and implemented for Widya Cipta: Jurnal Sekretari dan Manajemen, Volume 6 No. 1 Maret 2022 P-ISSN 2550-0805 E-ISSN 2550-0791 media selection, space size, and publication in media, which AIDA Model such as attention, interest, desire, and action is an populer hierarchy model for marketing and as guidance in marketing activity (Budiawan, Satria, & Simanjuntak, 2017) In another literature the concept of AIDA Model, can be controlled for successful implementation marketing strategies, this case concerating and developing for awarness of proposed product and help business to device marketing (Jiaqi, Teo, Tingting, & Jiaxun, 2021) In other side Effectiveness of promotion use for building brand sustainabilitybeside that The Effectiveness Promotion can be asa a strategic tool for marketing (Ahmed et al, 2019)…”
mentioning
confidence: 99%